Tekanan darah siswa sekolah dasar obes dan tidak obes di Kota Yogyakarta - Emy Huriyati; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2009)
Background: In adulthood, obesity is related to the increasing of mortality risk as the effect of cardiovascular diseases. Adulthood obesity is often started from childhood. Besides obesity causes, risk of cardiovascular are influenced by blood pressure as well.Objective: The study was proposed to compare blood pressure of obese and non-obese students.Method: The study was conducted among 52 obese and 52 non-obese students aged 9–12 years old matched with age and sex. Subjects were obtained through obesity screening among obese students. The criteria of obesity were BMI to age in or over 95 percentage of CDC 2000 standard. Blood pressure was measured three times at three different days with quicksilver sphygmomanometer. Its method was adjusted to Task Force on Blood Pressure in Children instruction.Results: Mean of systolic blood pressure of obese students was 109.2 (6.0) mmHg, higher than non-obese, 89.4 (6.9) mmHg. The different mean (CI 95%) of systolic blood pressure of both group was 19.9 (17.3-22.4) mmHg, p < 0.001. Mean of diastolic blood pressure of obese students was 72.4 (4.9) mmHg, while non-obese was 58.1 (8.1) mmHg. The different mean (CI 95%) of diastolic blood pressure of both group was 14.3 (11.6-16.9) mmHg, p < 0.001. Obese students had relative risk of systolic blood pressure (CI 95%) 22.5 (5.8-88.0) times higher than non-obese students. Relative risk of diastolic blood pressure of obese students (CI 95%) was 3.7 (2.4-5.8) times higher than that of non-obese students.Conclusion: Systolic and diastolic blood pressures of obese students were higher than that of non-obese students.